ARTVERTISING O EL ARTE COMO RECLAMO EN LA PUBLICIDAD: EL CASO DE LA CAMPAÑA ‘PRECIOBAJISMO’ DE LA EMPRESA LIDL - Dra. Gloria JIMÉNEZ-MARÍN,Dra. Elena BELLIDO-PÉREZ (Fonseca, Journal of Communication, 2023)
Art is a powerful means of communication used in many advertising campaigns to attract,generally, exclusivity values exclusivity to the advertised product. This text analyses a specific campaign where art is used as a slogan to refer to the low price by communicating that the product does not lose quality. This is the campaign ‘Preciobajismo’,carried out for the Lidl chain in Spain. By means of a discourse analysis, we study how the concept of art has been introduced in this campaign